Neutron reactor dosimetry monitoring by optical, nanostructural, and morphological changes of NiO thin films. (February 2023) - Dridi, W.; Jouini, K.; Daoudi, M.; Hosni, F.; Bignan, G.
Abstract: The effect of mixed neutron-gamma (n/γ) irradiation on microstructural, morphological, and optical properties of nickel oxide (NiO) thin films has been studied using UV–visible spectrophotometry, photoluminescence (PL) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). (NiO) thin films were irradiated in a Minerve reactor core at a doses range between 100 and 1000 Gy. The fast neutron dose, mainly due to elastic neutron scattering interactions in the range of 1–5 MeV, represents around 70% of the total irradiation dose. The results obtained show that the irradiation of the NiO thin films lead to significant changes in the optical properties, in the structure and in the morphology of the materials. The optical analysis shows visible range activation, which resulted in an increase in the absorbance of the band, centered around 645 nm. Otherwise, the integrated area of the band presents a linear dose response from 85 to 115 at dose ranging from 0 to 500 Gy. Furthermore, the band gap energy of the samples was linearly decreased from 3.52 eV to 3.44 eV by increasing the dose from 100 to 500 Gy, reaching 3.62 eV at 1000 Gy of irradiation n/γ dose. Urbach energy exhibited the same linear behavior, hence increasing from 372 to 400 meV. The variability of the integrated area, band gap energy and Urbach energy did not exceed 3% during 25 days. XRD analysis demonstrates that the crystallite size and the peak intensity for each preferred orientation planes (111) change with neutron-gamma radiation dose. The lattice parameter of preferential orientation (111) plane from rises linearly from 4.171 to 4.199 Å ± 0.0021 Å. Its variability is low, not exceeding 2%. SEM picture of irradiated NiO thin films shows the pore formation whose distribution increases with a dose level up to 500 Gy. Overall, the obtained results suggest that NiO thin films could considered as new alternative mean in neutron dosimetry application in nuclear reactor. Highlights: Nickel Oxide thin films irradiated by mixed n/γ radiation in the Minerve reactor core. Neutron induced radiation damage in NiO and produces displacements and vacancies. The neutron radiation up to 500 Gy stimulates a linear grain growth by dose radiation. NiO film as new neutron dosimetry monitoring by optical and microstructural behaviors. At 1000 Gy, the embrittlement phenomenon appears due to radiation damage neutron.